Perancangan Aplikasi Kompresi File Teks Menggunakan Algoritma Context Tree Weighting - Mayniar Albina (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Currently the use of applications as information is increasingly being used. but there is a problem that is often encountered, namely the need for a large space as a storage medium. Data compression is the process of converting a set of data into a coded form to save the need for data storage. Context Tree Weighting algorithm is a data compression algorithm. To determine the results of the compression process, compression ratio and space saving media are used. The results will be known, the compression ratio and space saving. In accordance with the results of the trials conducted, it can be seen that the data that was originally large in size can be compressed very well with the implementation of compression text files.